Research Trends and Mapping of Price Limits and Stock Prices in ASEAN 5: A Bibliometric Analysis - Mohammad Benny Alexandri; Umi Narimawati; Supriyanto Supriyanto (Jurnal Manajemen Indonesia, 2023)
The purpose of this study is to examine and analyze research trends and mapping of price limits and stock prices in ASEAN 5. This type of research is qualitative research. The research variables are Price Limit and Stock Price. The data collection technique used was bibliometric analysis from the Scopus database from 1996 to 2022. The number of research samples was 52 samples. The data analysis technique uses bibliometrics with the VOS viewer software program. The findings of this study indicate that 52 articles have been selected, with the number of publications increasing every year. Indonesia, Malaysia, the Philippines, Thailand and Singapore have an important role to play in the article price limits and share prices on Scopus as well as price limits reducing the volatility of stock returns, overcoming overreactions and not disrupting trading activities. Keywords: Price limits, Bibliometrics, Scopus, VOSviewer, ASEAN 5.